Commonwealth Catholicism : a history of the Catholic Church in Virginia - Fogarty, Gerald P. (University of Notre Dame Press, 2001)
Commonwealth Catholicism is the first comprehensive history of the Catholic Church in the State of Virginia. Distinguished historian Gerald P. Fogarty tells the story of Virginia's Catholics in the state's history, from the colonial period to the present. Using archival resources, Fogarty brings to life the events and characters that comprise the Church's colorful and often turbulent history.